Peran,Efektivitas,Kinerja PKSM dalam Keberhasilan Pengembangan KTH di Kota Pariaman dan Kabupaten Padang Pariaman - Stefani Belandinova Simatupang; Sri Mariya (JURNAL BUANA, 2026)
The 21st century is faced with environmental preservation challenges, degradation, soil erosion, pollution, other environmental threats. Through a community institution, the Forest Farmers Group (KTH) accompanied by PKSM has an important role in forest management to form community social change.PKSM role here is very important.Therefore the role of PKSM in KTH assistance needs to be explored to measure the level of efficacy of PKSM through the role and effectiveness of PKSM performance.The research method is using mix method, which conducted at KPHL Bukit Barisan Resort Kota Pariaman and Kabupaten Padang Pariaman.The research technique was done by conducting observation, interviews, as well as using questionnaire.Data analysis uses qualitative and quantitative descriptive analysis.The research result shows that the PKSM role and effectiveness are very high in guiding KTH, which can be seen from the success of Kota Pariaman and Kabupaten Padang Pariaman KTH in achieving all necessary indicators to meet the standard of KTH success